Qualidade pós-colheita do agrião da terra nos estádios “Microgreen” e “Baby leaf” - Araújo, Ana Beatriz Silva (2019)
A comparative study was carried out with upland cress (Barbarea verna) in three growth stages: microgreen (23 days after sowing), baby leaf (30 days after sowing) and adult (48 days after sowing). Non-pelleted seeds of upland cress (Barbarea verna) were sown on a phenolic foam substrate, covered with vermiculite, irrigated with water, kept in a greenhouse at room temperature (27ºC±7) and ambient light. Sixteen days after sowing, the seedlings were transferred to hydroponic system, irrigated with nutrient solution, and then three harvests were performed. The analyzes were: mineral profile, phenolic compounds, antioxidant capacity, coloration, pH, titratable acidity, total chlorophyll and total carotenoids. The upland cress in the microgreen stage presented 12 times more iron and twice as much magnesium, while in the baby leaf stage it presented higher calcium content and twice as much iron compared to the adult. There was also a higher presence of total carotenoids in the “microgreen” stage and a higher total phenolic content in the baby leaf stage. As for coloration, the adult upland cress had a darker and less intense shade of green compared to the upland cress harvested at earlier stages. The microgreen upland cress presented higher acidity than the upland cress in the other stages. These results suggest that the consumption of soil upland cress harvested in early stages may contribute to a higher intake of minerals and bioactive compounds.